THE EFFECT OF PROVIDING LIQUID ORGANIC FERTILIZER FROM FERMENTATION OF GOAT URINE AND COW URINE WITH MA 11 ACTIVATOR ON THE PRODUCTIVITY OF ODOT GRASS (Pennisetum purpureum cv. Mott) - Fikri Abdullah; Ludfia Windyasmara (Agrisaintifika: Jurnal Ilmu-Ilmu Pertanian, 2026)
This study examined the effects of applying liquid organic fertilizer (LOF), which is produced by fermenting a mixture of goat pee, cow urine, and the MA11 activator, on the growth and yield of odot grass (Pennisetum purpureum cv. Mott). With five replications and a single treatment factor consisting of four concentration levels, the study employed a completely randomized design (CRD). P0 (no LOF), P1 (10% LOF), P2 (20% LOF), and P3 (30% LOF) were the treatments. Plant height, leaf count, tiller count, fresh weight, and dry weight were among the observed metrics. The findings showed that applying LOF significantly increased the number of leaves, tillers, and plant height of odot grass. On fresh weight and dry weight, however, it had no discernible impact. When compared to the other treatments, P3 (30% LOF) produced the best growth response, making it the best treatment.